Wedge strategies in Russia-Japan relations. Issue 5 (22nd August 2022) - Dian, Matteo; Kireeva, Anna
Abstract: This article analyses wedge strategies in the context of Russo-Japanese relations. In particular, it looks at how both countries have sought to generate a dis-alignment in the opposing side, preventing further steps toward the consolidation of potentially threatening partnerships: the US-Japan alliance for Russia, and the Russia-China entente for Japan. After identifying the respective goals of Russia and Japan, the article examines the conditions that enable the success of wedge strategies. Looking at the case of Russia-Japan relations from 2012 to 2020, the article argues that a strategy constituted of a mix of positive economic and political incentives and a limited amount of coercion can succeed in producing a degree of dis-alignment in the opposing camp. Russia's strategy seems to be more productive than Japan's since Moscow has managed to minimize the effect of sanctions imposed by Japan and it has reduced political differences to mostly bilateral and regional issues. A greater level of cooperation with established partners for both Russia and Japan, and limited costs of wedging strategies, have resulted in dis-alignment but not a reversal of existing alignments. The article also indicates that in this case credibility issues do not fundamentally affect the degree of success of wedge strategies.